Morale and job satisfaction of academic librarians in Batangas province in relation to efficiency and productivity - Frane, Analiza A. 1972 - (2010)
Since the tremendous changes in the educational enterprise brought about by globalization have been evident in the Philippines, not only in the greater Manila area but in the CALABARZON areas as well, there is a need to investigate how the libraries and the librarians in the different educational institutions in the CALABARZON cope with the demands of the 21st educational enterprise. It is in this light that this study investigated the current situation of librarians in the CALABARZON, specifically in the Batangas province. This study was conducted to describe the present condition of librarians in the province of Batangas in terms of this job satisfaction, morale, and job performance. The study was also aimed at examining how the librarian's job satisfaction and morale relate with their efficiency and productivity. Correspondingly, the study sought to answer the following specific questions: 1.) What is the profile of the librarians in terms of: age, gender, civil status, educational attainment' length of service, current position title, salary and other benefits, faculty status?; 2.) What is the level of job satisfaction of academic librarians in terms of compensation, opportunities for professional advancement, general work condition, collaborative and interpersonal relationship?; 3.) What is the level of morale of academic librarians in terms of cohesive pride, leadership synergy, personal challenge?;4.) What is the level of performance of academic librarians?; 5.) Is there a significant relationship between the librarians' profile and their levels of morale? 6.)Is there a significant relationship between the librarians' profile and their levels of job satisfaction? 7.) Is there a significant relationship between the librarians' level of job satisfaction and their performance?; 8.) Is there a significant relationship between the librarians' level of morale and their performance?